Teoria de Markowitz e programação linear para formação de uma carteira ótima de investimentos - Dias, Denis Pereira (Universidade Federal de São Carlos, 2018)
The study presented in this dissertation aims to select an optimal portfolio of investments. To do so, we use the literature that deals with linear programming, coupled with Markowitz Modern Portfolio Theory to model and solve two linear programming problems that resulted in the composition of two portfolios, considering conservative and less conservative investor proﬁles. For the modeling of the problems, a technical analysis was performed on the assets that were previously selected for the composition of the portfolio. The selection of the assets took into account some statistical parameters, such as weighted arithmetic mean and correlation coeﬃcient. Considering that the experts’ forecasts indicated that the year 2018 would be favorable to investments in the Stock Exchange, the results obtained in this work agreed with this statement. However, as it is a technical analysis, it is concluded that the results presented do not guarantee a practical eﬃciency of the same, however, they serve to guide the investment activities.
Markowitz's theory and linear programing to formation an optmal portfolio of investiments
Keywords: Teoria de Markowitz; Programação Linear; Carteira Ótima de Investimentos; Markowitz’s Theory; Linear Programming; Optimum Portfolio of Investments; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA